Changing world air transport environment: searching for a proper balance: report (IATA MontrealCD, 1989)
Papers presented deal with topics such as the changing regulatory environment; changing structure of the industry; aviation in the 1990s; problems of the developing world; the world debt crisis; and aviation policies in the European Community. Conclusions and recommendations are included.
DC